2005
DOI: 10.1089/ars.2005.7.221
|View full text |Cite
|
Sign up to set email alerts
|

Factors Regulating Isoprostane Formation In Vivo

Abstract: Discovery of the F2-isoprostanes, a group of prostaglandin F2-like compounds biosynthesized from arachidonic acid nonenzymatically, has uncovered a new and novel facet of free radical biology. Some of these compounds are bioactive and thus may mediate adverse effects associated with oxidant stress. F2-Isoprostanes have also been shown to be reliable biomarkers of lipid peroxidation. Factors influencing their formation and metabolism have been studied to some extent, although much remains to be determined. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
91
1
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(102 citation statements)
references
References 129 publications
(170 reference statements)
9
91
1
1
Order By: Relevance
“…These studies support the concept that isoprostanes not only increase in models of ischemia-reperfusion but may also play a role in the pathophysiological sequelae of this injury [178].…”
Section: Cerebral Oxidative Nitrosative Inflammatory and Neurologicsupporting
confidence: 82%
“…These studies support the concept that isoprostanes not only increase in models of ischemia-reperfusion but may also play a role in the pathophysiological sequelae of this injury [178].…”
Section: Cerebral Oxidative Nitrosative Inflammatory and Neurologicsupporting
confidence: 82%
“…[113][114][115][116][117] Plasma levels as well as exhaled breath condensate were significantly higher when measured in the morning (i.e., after sleep) in patients with OSA compared to age-and weight-matched healthy obese subjects, while evening levels of 8-Isoprostanes were similar in both groups. 118 The positive correlation between morning levels of 8-isoprostane and AHI suggested an association between OSA and increased systemic and local levels of oxidative stress.…”
Section: Oxidative Stressmentioning
confidence: 95%
“…Reports have shown that F 2 -IsoPs are authentic, reliable biomarkers of lipid peroxidation and are useful in vivo indicators of oxidative stress in various clinical conditions, such as acute and chronic inflammation, ischemia/reperfusion injury, diabetes, and atherosclerosis (7,23,24,(63)(64)(65)(66)(67)(68). F 2 -IsoPs have also been used to assess in vivo oxidative response to various drugs, antioxidants, or dietary interventions for their free-radical-scavenging properties (7,23,24,(63)(64)(65)(66)(67)(68). Different methods for F 2 -IsoP quantification are available (23,68,69 ).…”
Section: Isoprostanesmentioning
confidence: 99%